(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Analysis of macroeconomic indicators of the Republic of Uzbekistan in recent years, management dynamics. The analysis studies the trends in the growth rates of gross domestic product (GDP), the volume of investments, the organization’s trade balance, employment and budget policy indicators. The article covers the comprehensive prospects of production in ensuring the macroeconomic situation.